Ecologia e conservação da vegetação de Cerrado às margens de rodovias - Paula, Monize Altomare de (2024)
The Cerrado, known as the Brazilian Savanna, stands out as the most biodiverse savanna in the world, hosting an impressive variety of plants and playing a crucial role in providing a range of essential ecosystem services. However, the biome has already lost more than half of its original area and faces multifaceted threats, primarily driven by agricultural expansion, urbanization, and climate change. Preserving this biodiversity hotspot and mitigating these threats requires innovative approaches that consider all available resources. This includes studying the ecology and conservation of vegetation in often neglected areas, such as road verges. Thus, in this thesis, I explored the ecological and conservation potential of these areas in the states of Minas Gerais and Goiás, aiming to understand their role in preserving the biodiversity and ecological functions of the Cerrado. Initially, I sought to understand the real potential of these areas adjacent to roads to support native Cerrado vegetation and consequently sequester above-ground carbon. Furthermore, I assessed the dynamics of this vegetation over time to determine whether areas occupied by native vegetation are being maintained, decreasing, or increasing over the years. I found that road verges in the Cerrado of Minas Gerais and Goiás harbor approximately 30% of native vegetation and store around 600 thousand tons of carbon. I also found that the coverage of native vegetation along the roadsides increased by about 2% over seven years, possibly due to the natural regeneration of abandoned areas. Subsequently, I aimed to understand the correlations between environmental factors and tree community biomass, as well as taxonomic, functional, and phylogenetic diversity in these environments. I found a complex relationship between environmental factors and the biomass and diversity of Cerrado trees, with variations observed in different metrics. However, I found evidence that soil fertility and the percentage of native vegetation in the surrounding landscape are factors that best explain the biomass and diversity (in their various facets) of the tree vegetation along road verges. Finally, I evaluated the impact of invasive grass species on the 4 structure and phylogenetic diversity of native Cerrado plants at the alpha and beta levels. I found a substantial reduction in phylogenetic diversity - both at alpha and beta levels - leading to a trend of phylogenetic homogenization. These patterns were noticeable only when considering both exotic and native species together. Furthermore, I observed that herbaceous plant communities in reserves have a more dispersed phylogenetic structure, while roadside communities have a more clustered structure due to the dominance of exotic species. Overall, my thesis not only reinforces the potential of roadside vegetation in Cerrado conservation but also highlights it as a model for better understanding how various environmental and anthropogenic factors shape Cerrado plant communities.